Solving the inverse problem of electrocardiography in a realistic environment - Jiang, Yuan (Karlsruhe transactions on biomedical engineering / Ed.: Universität Karlsruhe (TH) / Institute of Biomedical Engineering, 2010)
Heart disease is a leading cause of death worldwide. Straightforward information about the cardiac electrophysiology can help to improve the quality of diagnosis of heart diseases. The inverse problem of electrocardiography and the intracardiac catheter measurement are two ways to get access to the electrophysiology in the heart. In this thesis six research topics related to these two techniques are included.